Browsing Digital Video - Gupta, Anoop; He, Li-wei; Li, Francis; Rui, Yong; Sanocki, Elizabeth (1999)
Video in digital format coupled with digital/programmable playback devices presents opportunities for significantly enhancing the user’s viewing experience. For example, time compression can shorten the viewing length of a video and shot boundary frames can provide a visual index into the content. Such features have primarily been evaluated in isolation with a narrow set of video content types. We investigated as well as implemented the design of a software video browsing application that combines many such features. In addition, we evaluated its use in watching six different video content types and present the resulting data for analysis and discussion. The participants in the evaluation found the browser to be useful and effective for watching the different types of video in a limited amount of time. Also, the results show that both the experience of using the browser and value of each feature varies depending on the content type.